Value and Productive Labour in the Era of Digital Technologies - Søren Bøgh Sørensen (tripleC: Communication, Capitalism & Critique)
This article revisits the so-called digital labour debate to clarify and problematise the many different positions in this debate. Synthesising the most promising arguments from the different positions in the debate, the article outlines a theory of digital media usage as exploited, value-producing labour. In doing so, the article criticises the Autonomist Marxist tradition and argues for the utility of a value-form theoretical approach to the question of free digital labour. In conclusion, the article argues for more analytical attention to the ways in which technological developments in contemporary capitalism can engender new processes of production and thereby also new types of unpaid value-producing labour.